Biaxial weft-knitted fabrics as composite reinforcements: A review. (March 2017) - Hasani, Hossein; Hassanzadeh, Sanaz; Abghary, Mohammad Javad; Omrani, Elahe
Textile products are considered as an acceptable alternative for commonly used composite reinforcement due to their lightweight as well as relatively high specific strength and stiffness. Among the variety of textile structures which could be employed in composite manufacturing, the role of weft-knitted fabrics is almost very limited. This is because employing the weft-knitting technology would provide such structures with inferior mechanical properties due to their highly looped construction as well as low fiber volume fraction. But on other hand, it is important to be noted that some advantages such as high energy absorption, good impact resistance, and formability of knitted structures made the researchers to focus on investigating different methods by which the inferior mechanical properties of ordinary weft-knitted fabrics could be improved. Inserting the reinforcing yarns through the warp and weft direction of the knitted fabrics is considered as one of the effective solution for improving their mechanical behavior which eventually leads to a high potential product called as biaxial weft-knitted fabrics. In this literature, it is aimed to review different aspects of novel designed biaxial weft-knitted fabrics which could be suitable for a broad area of technical application such as composite reinforcements.